Analysis of umbilical cord blood gas in term and near term asphyxiated newborn babies - Ghimire, Amrit; Shrestha, Laxman; Shrestha, Merina (Journal of Patan Academy of Health Sciences, 2017)
Introductions: Birth asphyxia is failure breathing causing severe consequences or death. This study aims to determine the incidence of perinatal asphyxia in neonates with low Apgar and Hypoxic Ischemic Encephalopathy (HIE) in asphyxiated babies.Methods: This was a cross sectional study from November 1, 2010 to July 30, 2011. Babies with Apgar score of less than seven at five minute were enrolled in the study. Blood was drawn from umbilical cord artery for blood gas analysis. Neonates were followed up in every six hours for at least 48 hours. Staging of HIE according to Sarnat staging was done in babies with Apgar score of 7.2, 40% had between 7.1 to 7.2, 12% between 7 to 7.1 and remaining 2% had pH < 7. HIE developed in 22% (11/50) of the asphyxiated babies.Conclusions: More than 1/3rd (46%) of babies with low Apgar had low cord blood pH, 1/4th (26%) had base excess, and 22% developed features of HIE. Cord blood pH were better predictors than Apgar in asphyxiated babies.